2014
DOI: 10.1175/jamc-d-13-0202.1
|View full text |Cite
|
Sign up to set email alerts
|

Subkilometer Numerical Weather Prediction in an Urban Coastal Area: A Case Study over the Vancouver Metropolitan Area

Abstract: Numerical weather prediction is moving toward the representation of finescale processes such as the interactions between the sea-breeze flow and urban processes. This study investigates the ability and necessity of using kilometer-to subkilometer-scale numerical simulations with the Canadian urban modeling system over the complex urban coastal area of Vancouver, British Columbia, Canada, during a sea-breeze event.Observations over the densely urbanized areas, collected from the Environmental Prediction in Cana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 70 publications
2
46
0
Order By: Relevance
“…Never the less, this result could reflect the local area's characteristics (flat terrain, situated away from the coast) confirming previous studies Valari and Menut, 2008). In regions with more complex topography or those close to the coast, the resolution of the meteorological input could have a profound effect on the simulated meteorological conditions (Leroyer et al, 2014). We note here that the refinement in the resolution of the meteorological model from 0.5 to 0.1 • may not be sufficient for the CTM to simulate noticeable concentration responses.…”
Section: Sensitivity To the Resolution Of The Meteorological Input (Esupporting
confidence: 86%
See 2 more Smart Citations
“…Never the less, this result could reflect the local area's characteristics (flat terrain, situated away from the coast) confirming previous studies Valari and Menut, 2008). In regions with more complex topography or those close to the coast, the resolution of the meteorological input could have a profound effect on the simulated meteorological conditions (Leroyer et al, 2014). We note here that the refinement in the resolution of the meteorological model from 0.5 to 0.1 • may not be sufficient for the CTM to simulate noticeable concentration responses.…”
Section: Sensitivity To the Resolution Of The Meteorological Input (Esupporting
confidence: 86%
“…We note here that the refinement in the resolution of the meteorological model from 0.5 to 0.1 • may not be sufficient for the CTM to simulate noticeable concentration responses. For example Leroyer et al (2014) (see also references therein) observed that substantial changes in vertical and horizontal transport in an urban environment occurred mostly in the transition from resolutions of 2.5 to 1 km and even higher (250 m).…”
Section: Sensitivity To the Resolution Of The Meteorological Input (Ementioning
confidence: 99%
See 1 more Smart Citation
“…While we present the mean thermal characteristics of the coastal-urban environment here, additional work is necessary to study the turbulent transport of heat, momentum and moisture within the coastal-urban boundary layer. Current numerical weather prediction models used in the study of the urban boundary layer (e.g., Leroyer et al 2014;Gutiérrez et al 2015b;Ortiz et al 2016;Ramamurthy et al 2017b) lack a realistic representation of urban-coastal interactions, since boundary-layer parametrizations are unable to reproduce the thermal internal boundary layers observed. More effort and sustained observations are necessary to improve the predictability of the thermal conditions in the coastal-urban environment.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with aerosol backscatter in the boundary layer derived from lidar and CL31 measurements (McKendry et al, 2009;Tsaknakis et al, 2011) or from different ceilometers (Haeffelin et al, 2011), water vapor absorption was not considered, which is not critical as long as only mixing layer heights (e.g. Leroyer et al, 2013;Young and Whiteman, 2015) or cloud base heights (e.g. Martucci et al, 2010) are determined.…”
Section: Introductionmentioning
confidence: 99%